Brief Research Report: “Nothing About Us, Without Us”: A Case Study of the Outer Sanctum Podcast and Trends in Australian Independent Media to Drive Intersectional Representation - Symons, Kasey; Duncan, Sam; Sherry, Emma (Frontiers in Sports and Active Living, 2022)
Alternative and independent sports media platforms create custom content that reflects a diversity of voices and representation of athletes, sports and issues that are not covered in meaningful ways in traditional sports media. While these new media outlets often set out to redress the lack of diversity and intersectional approaches to traditional sports media, they are also seeking ways to drive even more change. This in an interesting and important movement to interrogate as these platforms are not only predominantly unfunded, passion projects created by those marginalized groups. This brief research report provides a case study into this emerging alternative media space and its impact in driving change in an ever-evolving sports media landscape. We also discuss the problematic nature of intersectional-redressing work falling on those who still occupy the margins. This report uses a case study of an independent Australian rules football platform, The Outer Sanctum podcast, to focus on these key areas. The case study investigates how this outlet has worked to increase the visibility and profile of marginalized and underrepresented voices discussing football in new ways. It follows their journey as they have taken steps to improve their own diversity, enacting their mantra “nothing about us, without us,” and proactively becoming more intersectional in their content producing journey. This research report will present key findings from the work of this media outlet to drive change and point to the learnings mainstream media can adopt to meaningfully embed intersectional approaches to sports media as core business.